How does legalization of physician assisted suicide affect rates of suicide? - Jones, David Albert; Paton, David (Lippincott, Williams & Wilkins, 2015)
Objectives: Several US states have legalized or decriminalised physician assisted suicide (PAS) whilst others are currently considering permitting PAS. Although it has been suggested that legalization could plausibly lead to a reduction in total suicides and to a delay in those suicides which do occur, to date no research has tested whether these effects can be identified in practice. The aim of this paper was to fill this gap by examining the association between the legalization of PAS and state-level suicide rates in the USA between 1990 and 2013.